Landscape structure evolution and ecological risk evaluation of oasis desert cities: A case study of Tiemenguan city - Mingyue Sun; Hongguang Liu; Yingsheng Dang; Ping Gong; Pengfei Li; Rui Fang; Huan Cao; Xiang Li; Hanji Xia; Fuhai Ye; Yong Guo (PLoS ONE, 2025)
The rapid development of oasis desert cities adversely affects fragile ecosystems, preventing regional sustainable development. This study investigates the spatiotemporal evolution characteristics and potential quantitative relationship between oasis landscape structure (OLS) and the ecological risk index (ERI) and the trend in different development scenarios in Tiemenguan City, a typical oasis city in an arid zone in northwestern China, from 1990 to 2020. We calculated the ERI thresholds for different landscape types, classified ecological risk levels, and examined the factors influencing ecological risk. The normalized difference vegetation index (NDVI) thresholds were NDVI ≥ 30% for oases, 10% <NDVI < 30% for transition zones, and NDVI ≤ 10% for desert areas. Under government control, transitions from cropland, woodland, and grassland to built-up and unused land decreased by 20%, whereas conversions from unused land to cropland, woodland, and grassland increased by 30%. The results showed the following: (1) The oasis area expanded continuously from 175.5 km2 to 345.3 km2 during 30 years. The transition and desert zones decreased by 49.7% and 37.9%, respectively. The ERI decreased and was strongly correlated with the OLS. The thresholds of the ERI in the oasis zone-transition zone and the transition zone-desert zone were 0.08–0.085 and 0.111–0.118, respectively. (2) Socioeconomic factors, including infrastructure expansion, population density, and GDP, were dominant influences, contributing 64% to the ERI, whereas the influence of natural factors such as climate declined. (3) The low-ERI areas increased by 3.3% under government control, and the transition zones increased significantly, slowing the growth rate of the oasis zone. This study quantitatively evaluated the landscape types’ ecological risk levels and analyzed the effects of dynamic migration on the landscape type stability. This paper provides a systematic research framework for ecological risk assessment of various landscape types in oasis desert cities and a scientific basis for ecological conservation and related research.